2014
DOI: 10.1111/1756-185x.12419
|View full text |Cite
|
Sign up to set email alerts
|

Childhood onset systemic lupus erythematosus: how is it different from adult SLE?

Abstract: About 20% of systemic lupus erythematosus (SLE) starts in childhood and children have less gender bias in favor of females as compared to adults. Systemic manifestations, nephritis, neuro-psychiatric disease and cytopenias are more common in children at presentation than adults. Since most children develop lupus in their early adolescence, dealing with the diagnosis of an unpredictable lifelong disease during this phase of life is challenging. Physicians must recognise specific medical and social needs of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 74 publications
1
73
0
10
Order By: Relevance
“…Patients with a history of renal and neuropsychiatric manifestations had a younger age of onset of SLE. Other studies have also shown that renal and neurological manifestations are more common in SLE patients with a younger age of disease onset [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with a history of renal and neuropsychiatric manifestations had a younger age of onset of SLE. Other studies have also shown that renal and neurological manifestations are more common in SLE patients with a younger age of disease onset [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, poor adherence is associated with lower health-related quality of life, increased health care utilization, health care costs, and unnecessary medication changes [3][4][5]. Optimizing medication adherence in individuals with cSLE is critical because, compared with adult-onset SLE patients, they have a more severe and prolonged disease course with more disease-related organ damage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fever is a common symptom in pediatric SLE, and it is di cult to distinguish between an SLE are and febrile infection [7]. Some infections may produce systemic manifestations mimicking SLE, either superimposed upon or triggering a are [8].…”
Section: Introductionmentioning
confidence: 99%